Forage legumes in agropastoral production systems within the subhumid zone of Nigeria - Mohamed-Saleem, M.A. (International Development Research Centre, 1985)
Land use in the subhumid zone (SHZ) of Nigeria is rapidly changing as a result of increasing influx of both arable farmers and pastoralists from areas of high density in the country. Because land is owned by arable farming communities, traditional grazing lands tend to be heavily pressurized by increasing settled and nomadic animals. Long-term well being of the livestock industry in the SHZ will therefore depend on the integration of fodder and crop production. Methods of improving fodder through use of Stylosanthes in agropastoral systems is described in the cropping and fallowlands areas. As crop and livestock enterprises are normally handled by separate ethnic groups, the need to demonstrate direct benefits to cropping through adoption of a forage legume in cropping patterns is suggested as an incentive to invest in fooder improvement in arable areas. The need for screening other legumes for agropastoral production systems is emphasized because of the vulnerability of the available stylo cultivars to anthracnose.